Dose–response curves for analyzing of dicentric chromosomes and chromosome translocations following doses of 1000 mGy or less, based on irradiated peripheral blood samples from five healthy individuals. (13th October 2017) - Abe, Yu; Yoshida, Mitsuaki A; Fujioka, Kurumi; Kurosu, Yumiko; Ujiie, Risa; Yanagi, Aki; Tsuyama, Naohiro; Miura, Tomisato; Inaba, Toshiya; Kamiya, Kenji; Sakai, Akira
Abstract: In terms of biological dosimetry at the time of radiation exposure, the dicentric chromosome (Dic) assay (DCA) is the gold standard for assessing for the acute phase and chromosome translocation (Tr) analysis is the gold standard for assessing the chronic phase. It is desirable to have individual dose–response curves (DRCs) for each laboratory because the analysis criteria differ between laboratories. We constructed the DRCs for radiation dose estimation (with three methods) using peripheral blood (PB) samples from five healthy individuals. Aliquots were irradiated with one of eight gamma-ray doses (0, 10, 20, 50, 100, 200, 500 or 1000 mGy), then cultured for 48 h. The number of chromosome aberrations (CAs) was analyzed by DCA, using Giemsa staining and centromere-fluorescence in situ hybridization (centromere-FISH) and by chromosome painting (chromosome pairs 1, 2 and 4) for Tr analysis. In DCA, there was large variation between individuals in the frequency of Dics formed, and the slopes of the DRCs were different. In Tr analysis, although variation was observed in the frequency of Tr, the slopes of the DRCs were similar after adjusting the background for age. Good correlation between the irradiation dose and the frequency of CAs formed was observed with these three DRCs. However, performing three different biological dosimetry assays simultaneously on PB from five donors nonetheless results in variation in the frequency of CAs formed, especially at doses of 50 mGy or less, highlighting the difficulty of biological dosimetry using these methods. We conclude that it might be difficult to construct universal DRCs.